Kempen â€œKepimpinan melalui Teladanâ€semasa Era Pemerintahan Tun Dr. Mahathir Mohamad di Malaysia (Sains Humanika, 2017)
This study on leadership examines the purposes of the Leadership by Example Campaign during Tun Dr Mahathir Mohamadâ€™s tenure as Prime Minister of Malaysia. Leadership studies are interested in people from all walks of life because the struggles of the brave and wise leaders have become the source of legends and myths.Therefore, the issue of leadership is an important agenda for both the private and public sectors ineither developed countries or developing countries. The issue becomes more acute due to a constantly changing environment.In fact, every change that happens in the environment becomes a constant challenge for leaders in all sectors.In the context of the political leadership in Malaysia, the position and interests of UMNO and Barisan Nasional led by Tun Dr Mahathir Mohamad was quite evident because it was the leadership that had led the country for a long period of time to the extent that it was considered as a bridge connecting two generations of UMNO. However, people who were born in the 1980s only recognised one Prime Minister and four Deputy Prime Ministers until the day of his retirement. Thus, the study found that the Leadership by Example Campaign introduced by Tun Dr Mahathir Mohamad that aimed for instilling and cultivating effective leadership was emulated, appreciated and practised by all levels of society.In general, this study used a qualitative approach. While, this data was gathered through document review and analysis of the content to obtain the results. The Leadership by Example Campaign was a noble effort from Tun Dr Mahathir Mohamad to foster a spirit of discipline and establish the identity of every Malaysian to be able to stand tall together with other nations.Â
Keywords: Leadership by example campaign; Tun Dr Mahathir Mohamad; Malaysia